2019
DOI: 10.1111/ejss.12904
|View full text |Cite
|
Sign up to set email alerts
|

Managing grazing intensity to reduce the global warming potential in integrated crop–livestock systems under no‐till agriculture

Abstract: Agricultural intensification has been associated with increased greenhouse gas (GHG) emissions. Using integrated crop-livestock systems (ICLs) under no-till agriculture can increase soil organic carbon (SOC) accumulation, thereby helping mitigate such emissions. The aim of this study was to assess the net global warming potential (net GWP) of no-till ICLs at variable grazing intensities of winter black oat pasture in a subtropical ecosystem. A 3.5-year field experiment involving three different grazing intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 59 publications
(95 reference statements)
0
22
0
2
Order By: Relevance
“…In another long‐term experiment (9 years), Ramalho et al (2020) also found that grazing did not compromise SOC gains under NT on a Ferralsol (Food and Agriculture Organization (FAO) soil classification). Ribeiro, Ibarr, Besen, Bayer, & Piva (2020) carried out an on‐farm assessment of net global warming potential (GWP) in NT integrated crop–livestock systems on a Ferralsol, and reported that moderate grazing was optimal for reducing GWP due to the SOC accumulation in comparison to no, light or intensive grazing options.…”
Section: Assessment Of Nt Impacts In Combination With Grazing Fertilmentioning
confidence: 99%
“…In another long‐term experiment (9 years), Ramalho et al (2020) also found that grazing did not compromise SOC gains under NT on a Ferralsol (Food and Agriculture Organization (FAO) soil classification). Ribeiro, Ibarr, Besen, Bayer, & Piva (2020) carried out an on‐farm assessment of net global warming potential (GWP) in NT integrated crop–livestock systems on a Ferralsol, and reported that moderate grazing was optimal for reducing GWP due to the SOC accumulation in comparison to no, light or intensive grazing options.…”
Section: Assessment Of Nt Impacts In Combination With Grazing Fertilmentioning
confidence: 99%
“…Thus, the nutrient cycling, in the pasture phase, starts when the first leaf senesces and returns to soil in form of nutrients and organic matter, thereby the nutrient cycling occurs constantly throughout the grazing period. According to Ribeiro et al (2019), the grazing period in an ICLS can increase the soil carbon stock and accelerate the nutrient cycling due to the continuous pasture growth and the higher forage yield stimulated by grazing.…”
Section: Forage Mass and Botanical Compositionmentioning
confidence: 99%
“…Previous GWP evaluations of ICL systems have been conducted in Brazil, where pasture-based production of cattle (Bos taurus) is common (Cardoso et al 2016). In southern Brazil, Ribeiro et al (2019) found ICL systems under a black oat (Avena strigosa Schreb.) -soybean (Glycine max L.) rotation and notill management reduced net GWP under moderate grazing compared to intensive grazing (0.09 vs. 4.92 kg CO 2equiv.…”
Section: Introductionmentioning
confidence: 99%